How to set up and run a multi-centre trainee-led collaborative project. Issue 2 (4th May 2022) - Nasser, Ahmed A H; Archer, James E; Chauhan, Govind Singh; Thompson, Calum; Osman, Khabab; Nandra, Rajpal; Dewan, Varun
Abstract: The multi-centre trainee-led collaborative research model improves the generalizability of results, efficiency of data collection, quality of data and sample size. Although an enormous amount of effort and resources are sometimes required, the final results lead to a standard that is unachievable by conventional studies. In this article, we summarize a step-by-step guide on how to set up and run a multi-centre trainee-led collaborative project.